1970
DOI: 10.13057/nusbiosci/n050101
|View full text |Cite
|
Sign up to set email alerts
|

Macro-fungal diversity and nutrient content of some edible mushrooms of Nagaland, India

Abstract: Abstract. Kumar R, Tapwal A, Pandey S, Borah RK, Borah DP, Borgohain J. 2013. Macro-fungal diversity and nutrient content of some edible mushrooms of Nagaland, India. Nusantara Bioscience 5: 1-7. The northeast region of India abounds in forest wealth, including variety of flora and fauna. The high humidity during monsoon period provides ideal atmospheric conditions for the growth of diverse group of macrofungal fruit bodies. Nagaland, the northeastern state of India is rich in biodiversity and encompasses larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1970
1970
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…The study promotes awareness to harvest and exploit this underutilized local resource, which will provide nutritious food and employment opportunities especially to the disadvantaged groups (i.e. unemployed and old people) (Kumar et al, 2013;Sachan et al 2013;Tanti et al, 2011;Tibuhwa, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study promotes awareness to harvest and exploit this underutilized local resource, which will provide nutritious food and employment opportunities especially to the disadvantaged groups (i.e. unemployed and old people) (Kumar et al, 2013;Sachan et al 2013;Tanti et al, 2011;Tibuhwa, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms are highly prized delicacy of the state. Very few works has been done on wild edible mushrooms in Nagaland (Kumar et al, 2013). In most of these reports the mushroom resources are ill presented.…”
Section: Introductionmentioning
confidence: 99%
“…The carbohydrate content of edible mushrooms usually ranges from 40.6% to 53.3% of dry weight (Khanna et al 1992; Several dozen species of wild fungi are sold in the market of north-eastern India and most are ectomycorrhizal (Tanti et al 2011). Kumar et al (2013) collected fifteen edible/ medicinal mushrooms of Nagaland and worked out them for protein, crude fiber, carbohydrate and ash content. Tapwal et al (2013) made a collection of 30 macrofungal species belonging to 26 genera from wet evergreen forests of Assam, northeastern India and investigated their ecological relationship with higher trees and documented their utilization as per available literature.…”
Section: Frequency Of Species and Proximate Analysismentioning
confidence: 99%
“…The diversity of Russula species has been explored in different parts of the west district of Sikkim, India (Das 2010;Das et al 2010;Das andVerbeken 2011, 2012). Recently, three new species, i.e., R. sharmae, R. sikkimensis, and R. dubdiana were reported from Sikkim, India (Das et al 2013) We collected, identified and analyzed the nutrient content of fifteen mushroom species from different forest of Nagaland recently (Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A. delicata is a delicious edible mushroom utilized as a potential nutritious food source and traditional medicine with dominance in some regions of Africa and Eastern Asia, particularly China and India [1][2][3]. In the past mushrooms were used as a local food resource [3].…”
Section: Introductionmentioning
confidence: 99%